Are the Deterrent Effects Could Effective for Reduce Corruption Criminal Action in Indonesia? - Wibowo, Padmono; Sutawijaya, Dimas Dhanang; Prabowo, Yudha Cahyo; Jayanti, Nur Ria Tri (International Journal of Psychosocial Rehabilitation, 2020)
So far the approach through punishment as a deterrent effect is considered as one of the solutions in overcoming the problem of corruption in Indonesia. However, how optimistic is the deterrent effect of criminal punishment can reduce the level of corruption in Indonesia. This research was conducted to find out the decrease in the level of corruption and how optimal the prevention of corruption through the deterrent effect of the criminal deterrent effect in overcoming the problem of corruption in Indonesia. This research uses descriptive qualitative research methods. The results of this study are in the form of an analysis of how optimistic the deterrent effect of the criminal deterrent effect on eradicating corruption in Indonesia. It is expected that through this research can provide an overview of reducing the level of corruption and how optimal the prevention of corruption from giving criminal penalties to perpetrators of corruption and also how much deterrence effect is given to others so as not to commit corruption through criminal penalties. It is also hoped that this research can provide the best solution in preventing and reducing criminal acts of corruption in Indonesia